(untitled) (The Peerian Journal, 2024)
The relationship of Ahl al-Dhimmah (Christians, Jews and other non-Muslims) with the Mamluk state in Egypt and the Levant (1250-1517 AD) was complex, ranging from tolerance to discrimination according to political, social and religious circumstances. This relationship can be summarized in several key points: The legal status of the Ahl al-Dhimmah: Ahl al-Dhimmah lived under the "dhimmah" system, which granted them the freedom to practice their religion and protect their property in exchange for paying the jizya, a type of tax for non-Muslims. They had the right to live in peace, but were bound by certain legal restrictions that separated them from Muslims. Tolerance and coexistence: In periods of stability, relations between the Mamluks and Ahl alDhimmah were characterized by relative tolerance. Many dhimmis held important administrative and financial positions in the Mamluk state, such as tax and finance administration, due to their skills in these fields. This contributed to building a beneficial relationship between the two parties, as the Mamluks relied on the dhimmis’ expertise in administration and economics. Discrimination and social restrictions: Despite the relative tolerance, there were social and religious restrictions imposed on the Ahl al-Dhimmah. For example, they were required to wear distinctive clothing and were prohibited from building new churches or temples without special permission. They were also banned from certain jobs and senior military and political positions. Turbulent periods and persecution: Dhimmis were sometimes persecuted, especially during periods of political or religious unrest. In such periods, more restrictions were imposed on them, and sometimes their property was looted or they were expelled from certain areas. For example, the late Mamluk period saw an upsurge in discrimination against Ahl al-Dhimmah as a result of economic pressures and wars